2016
DOI: 10.1063/1.4967201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu buffer layer on magnetic anisotropy of cobalt thin films deposited on MgO(001) substrate

Abstract: Cobalt thin films with 5 nm thickness were prepared on single-crystal MgO (001) substrates with different thickness Cu buffer (0 nm, 5 nm, 10 nm, 20 nm). The structure, magnetic properties and transport behaviors were investigated by employing low-energy-electron-diffraction (LEED), magneto-optical Kerr effect (MOKE) and anisotropic magnetoresistance (AMR). By comparing the magnetic properties of the sample as-deposited (without Cu buffer layer) one with those having the buffer Cu, we found that the magnetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Matter 2020, 5, 71 3 of 10 and at a positive saturation, here described as ΔMT,sat. This value is related to the torque working on the magnetization, which is proportional to sin(θH−θM) with the angle θH of the applied field and the angle θM of the magnetization [21] and can thus be used to understand the anisotropy of a sample qualitatively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matter 2020, 5, 71 3 of 10 and at a positive saturation, here described as ΔMT,sat. This value is related to the torque working on the magnetization, which is proportional to sin(θH−θM) with the angle θH of the applied field and the angle θM of the magnetization [21] and can thus be used to understand the anisotropy of a sample qualitatively.…”
Section: Resultsmentioning
confidence: 99%
“…The simulation revealed angular ranges in which peaks of different shapes were visible in the transverse magnetic components and allowed for measuring the difference between M T at a negative and at a positive saturation, here described as ∆M T,sat . This value is related to the torque working on the magnetization, which is proportional to sin(θ H −θ M ) with the angle θ H of the applied field and the angle θ M of the magnetization [21] and can thus be used to understand the anisotropy of a sample qualitatively.…”
Section: Methodsmentioning
confidence: 99%
“…4(c, g and d, h)), the polar plots for coercive field and M rem /M sat hysteresis loops showed increasingly isotropic characteristics. The observed change in magnetocrystalline anisotropy feature from cubic to isotropic can be attributed to strain and the microstructural evolution as discussed in references [1], [13], [17].…”
Section: B Magnetic Propertiesmentioning
confidence: 79%
“…Finally it would be interesting to extend this work for dif ferent thickness of cobalt films deposited on patterned sub strates with different buffer layers. Buffer layers are expected to control the growth direction/texture of cobalt films [4,[5][6][7]. With increasing thickness of cobalt films, it is reported in con tinuous epitaxial films that the magnetization rotates from in plane to outofplane direction due to the strong perpendicular magnetocrystalline anisotropy [8].…”
Section: Resultsmentioning
confidence: 99%
“…Also substrate temperature, use of buffer layers, deposition rate etc, are the parameters that can be manipulated in thin film growth for desired properties [1]. For example, buffer layers such as Ta, Cu, Au, Ru etc, can promote a specific structure or orientation and hence better magnetic properties are reported in cobalt based thin films and multilayers [4,5,6,7,8]. Hehn et al have studied epitaxial hcp cobalt films and reported the develop ment of perpendicular magnetic anisotropy with increasing thickness [8].…”
Section: Introductionmentioning
confidence: 99%